Pendampingan Labelisasi dan Pencatatan Koleksi Perpustakaan Pada Perpustakaan Sekolah - Muhammad Muhammad; Ainur Latifah; Eva Nurjannah (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2023)
This community service is carried out in the library of SMP Negeri 2 Sangatta Utara in the form of assistance in managing library book collections. The aim is to assist in inventorying, classifying, inputting data, labeling, and compiling the library book collection of SMP Negeri 2 Sangatta Utara. The method used in this service is a participatory Action Research research method. Participatory Action Research is a service research activity where the author is directly involved in a participatory manner as a mentor at the service location. The results are: First, the library at SMP Negeri 2 Sangatta Utara is still lacking in book collections where most of the existing book collections are textbooks according to class. Second, the arrangement of the books is still irregular so that in the shelving process we rearrange the previous books based on their classification. Third, the data input is still in the form of a ledger where if you look at the modern situation, almost all activities have been done digitally. It is hoped that further PkM activities can contribute more in fulfilling book collections and library management.